Satisfacción de padres con visitas domiciliarias mediante la estrategia Aprendo en Casa de la Institución Educativa N° 713 distrito de Yavarí 2021 - Yumbato Grandez, Keslena (2023)
The main objective of the present research was to describe the level of satisfaction of parents with home visit in the I Learn at Home strategy in the Educational Institution No. 713 Bilingual Intercultural in Erené, Yavarí district in the year 2021. The type research has been the descriptive type with a field, univariate and cross-sectional design. For the purposes of the work, the population was 60 parents belonging to the educational institution, being themselves the ones who made up the sample. In order to collect the data, the survey technique was used by means of a questionnaire, which has been validated by experts on the subject. It is concluded that in general the level of satisfaction of the parents of the children of the Initial Educational Institution N°713 Bilingual Intercultural that participated in the investigation has 43.3% are very satisfied with the home visit of the teacher; 36.7% satisfied and 20.0% not very satisfied with the applied strategy. Result that confirms that the level of satisfaction with the application of this strategy to provide the educational service during this pandemic is high.